2018
DOI: 10.1007/s12178-018-9480-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Risk of Recurrent Patellar Dislocation

Abstract: Several demographic risk factors (age, skeletal immaturity, sex, bilaterality), mechanism of injury, and anatomic risk factors (trochlear dysplasia, patella alta, excessive tibial tubercle lateralization, increased patellar tilt) have been recognized. The combination of different risk factors, their relative contribution to instability, weightage of each factor, and multivariate analysis have led to the development of a prediction model and instability scoring system. If recurrent instability and poor outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(67 citation statements)
references
References 39 publications
3
63
0
1
Order By: Relevance
“…Moreover, increased lateralization of the tibial tuberosity can be evaluated throughout the measurement of the TT-TG distance. TT-TG value is independent of the patient's height and weight [21].…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, increased lateralization of the tibial tuberosity can be evaluated throughout the measurement of the TT-TG distance. TT-TG value is independent of the patient's height and weight [21].…”
Section: Discussionmentioning
confidence: 94%
“…TD has consistently been associated with PI, and several studies 4,12,20,21,26,27,31 have identified it as either the primary or one of the strongest associated risk factors for instability or recurrent instability. Dejour et al 14 observed that in a population of patients undergoing surgical stabilization for PI, 85% had 2 radiographic signs of TD and 96% had 1 sign of TD, versus only 6% of the control group with any radiographic signs of TD.…”
Section: Discussionmentioning
confidence: 99%
“…1,17,35 PI is multifactorial, with several identified risk factors such as age, activity level, trochlear dysplasia (TD), patella alta, patellar tilt, and coronal and rotational plane malalignment. 4,12,21,24,31,36,41 Of these risk factors, TD has been consistently identified as having the strongest association with recurrent PI. 6,12,14,21,26,27 Recently, some studies 9,25,40 have shown that TD alters the patellofemoral joint such that other radiographic parameters used to characterize PI, in particular the tibial tuberosity to trochlear groove (TT-TG) measurement, are changed relative to the amount of TD present.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…review by Parikh et al 15 It is imperative to continue to search for the optimal treatment of a first-time dislocation patient, understanding that each patient will have a unique pattern of injury and risk factors that will deserve patient-specific treatment.…”
Section: Editorial Commentarymentioning
confidence: 99%